Antibacterial applications and Comparative Study for Adsorption Phenol Red Dye Using Spinel Co1-xMxFe2O4 Nano Composites (M= Cd, Ag) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This work concerned with the study of adsorption of phenol red dye by using spinel Co1-xMxFe2O4 was prepareby Co-precipitation method at different ratios of (0.2:0.8, 0.5:0.5, 0.8:0.2) and calcinations at temperature600 C0 for three hours. The conclusion showed that (0.5:0.5) percentage has high activity than other ratioat different temperature. The prepared powder was differentiated by X-ray diffraction, Fourier TransformTechnique (FT-IR), UV-Visible Spectroscopy, Scanning Electron Microscopy (SEM), Energy DispersiveSpectroscopy (EDS), Atomic Force Microscope (AFM), high performance liquid chromatography (HPLC)were also studied for all spinel. X-ray and Electron Microscopy studies showed the average size of thegranules prepared for the composite in this manner (17.44 for Cd and 37.55 for Ag)